Analisis Pengaruh Modal Usaha terhadap Perkembangan Usaha UMKM (Usaha Mikro Kecil Menengah) Wilayah Pesisir Madura - Yuliana, Rika; Hadyarti, Vidi (JURNAL ADMINISTRASI KANTOR, 2023)
Micro, Small and Medium Enterprises (MSMEs) one kind of business which make an important role to the country's economic. Therefore, it must continue to develop its business by understanding the factors that need to be considered. The conducted of this research is due analyze the relationship between business capital and the development of SMEs in the coastal area of Madura. The data is sourced from Micro, Small, Medium Enterprises as the subject of this research around the slopeng beach with 50 respondents. The results of the study indicate that there is a positive influence from business capital to the development of micro, small, and medium enterprisess around Slopeng beach of Madura.                                    Keywords : Business Capital, Business Development Micro, Micro Small Medium Enterprises.